Special criminology measures for preventing unvoluntary leaving a military unit or place of service - P. I. Tkachenko (Bulletin of Kharkiv National University of Internal Affairs)
Voluntary abandonment of a military unit or place of service is a serious problem in the field of military discipline, operational readiness and defense capability of the army. This problem can have a negative impact on the effectiveness of military operations, the security of the country and trust in the representatives of the military management and defense sector. The spread of the specified type of criminal act forces lawyers to investigate the nature of the commission of the crime provided for in Art. 407 of the Criminal Code of Ukraine (hereinafter referred to as the Criminal Code of Ukraine), criminological characteristics, dynamics, the person-criminal, as well as prevention measures, among which it is possible to single out the special criminological orientation, which can be recognized as narrowly directed and designed to effectively solve the tasks.